PROFESSOR, REZADOR E BENZEDOR: A CULTURA FAXINALENSE (1906 - 1988) - Rodrigues, Paulo Gelson (2017)
This dissertation starts from the perspective of the history of everyday life. It results of the attempt to give visibility to the ordinary man historical agent, carrier of living and experiences hidden among the mass of the homogeneity. In this study, we will accompany Albino Gonçalves`s life trajectory, a presumably common man who, for us, was considered detachable for his performances in various sectors of everyday life. Lived eighty two years. Most of that time lived in the interior of the faxinalense space, in the city of Rebouças/PR. In this period of eight decades, he has taken courses in the area of education, exercised his composer talents, led religious practices and ended his days as a healer/prayer. Produced texts written in prose and verse. Registered, collected and stored various types of documents related to the actintives performed. These written records wil allow you to identify the paths that are part of the character s region. A region constructed from the correlation of everyday practices. The practices performed by the character and his interlocutors were classified as forms of consumption, silent and cunning, that employ, in their way, the products imposed by a dominant order. The history is the road that we wil follow to capture actions of appropriation, invention, cheating, against a logic that is imposed on the practitioners of this region. Using the documents of the character, oral interviews, various sources and the conceptual apparatus of Michel de Certeau, we aim to recompose some paths and to understand the ways in which the ambient is narrated by Albino and his interlocutors. The dissertation is included in the studies of history and region. It is a question of thinking of space as a practiced place and of the trajectory as a practitioner of space/region.